Inovasi Model Problem Based Learning (PBL) dalam Meningkatkan Pemahaman Teks Pidato pada Siswa di SMP Negeri 1 Banjarmasin - Norhidayah Norhidayah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to describe the innovative application of the Problem Based Learning (PBL) model in improving the understanding of speech texts in grade VIII students of SMP Negeri 1 Banjarmasin. The study uses a descriptive qualitative approach supported by quantitative data in the form of student learning outcomes. Data sources include lesson planning documents (RPP), the "Understanding Speech" teaching module compiled by Istiqomah HM, and student learning outcomes. The learning process is carried out through PBL stages which include problem orientation, organizing students in group work, investigation, compiling and presenting results, and learning reflection. The results show that the application of the PBL model is able to improve students' understanding of the structure, content, and linguistic rules of speech texts. The average individual score reached 96.84 with most students obtaining a score ≥ 80. In addition to improving academic achievement, the PBL model also has a positive impact on students' critical thinking skills, collaboration, and communication skills. Although technical obstacles and differences in literacy levels were still found, this model is considered effective and worthy of further development in Indonesian language learning at the junior high school level.